Enucleation in Asian Indian patients: a histopathological review of 2009 cases - Kaliki, Swathi (Eye (Lond), 2018)
OBJECTIVE: To review the indications of enucleation in Asian Indian patients and study the trend over the 22-year period. METHODS: Retrospective study of 2009 patients who underwent enucleation. RESULTS: The mean age at presentation of patients who underwent enucleation was 155 months The histopathology diagnosis included a benign tumor (n = 22, 1%), malignant tumor (n = 1472, 73%), acute trauma (n = 93, 5%), retinal vascular disease (n = 50, 3%), inflammatory/infective pathology (n = 33, 2%), or other miscellaneous/non-specific diagnosis (n = 460, 23%). There was a good correlation between the clinical and histopathology diagnoses at 96%. The most common indication for enucleation in young patients ( ≤ 20 years) was retinoblastoma (n = 1257, 82%; p < 0.001), atrophic bulbi or phthisis bulbi (n = 163, 39%; p < 0.001) in middle-age adults, and uveal melanoma (n = 25, 42%; p < 0.001) in older adults. Over the years, there was a decreasing trend of enucleations for atrophic bulbi/phthisis bulbi/painful blind eye (33% from the years 1996 through 2000 to 7% from 2010 to 2018; p < 0.001) and acute trauma (3% from the years 1996 through 2000 to < 1% from 2010 to 2018; p < 0.001) and an increasing trend for intraocular tumors including retinoblastoma (56% from the years 1996 through 2000 to 73% from 2010 to 2018; p = 0.01) and uveal melanoma (3% from the years 1996 through 2000 to 11% from 2010 to 2018; p < 0.006). CONCLUSION: In Asian Indian population, malignant tumors remain the most common indication for enucleation in young and older patients, while desire for better cosmesis with customized ocular prosthesis is the main indication for enucleation in middle-age adults.